Myeloma proteins from NZB and BALB/c mice: structural and functional differences. - Loh, E (1979)
Structural and functional analyses of myeloma immunoglobulins from inbred BALB/c mice and humans have provided important insights into the structure of the antibody molecule and the expression and evolution of antibody genes. One important question concerning these analyses is whether the myeloma process selects, in a nonrandom manner, the lymphocytes to be transformed. The availability of myeloma tumors in a second inbred strain of mouse, NZB, permits us to approach this question. In this respect. the NH2-terminal amino acid sequences of 27 kappa light chains as well as data relating to the antigen-binding properties and immunoglobulin class distribution of NZB myeloma proteins are presented and compared with similar data from the BALB/c mouse. These studies suggest that the myeloma proteins from the BALB/c and NZB mice constitute two populations of immunoglobulins with distinct functional and structural properties. The implication of this observation are discussed.